2015
DOI: 10.1371/journal.pcbi.1004005
|View full text |Cite|
|
Sign up to set email alerts
|

Systems Level Analysis of Systemic Sclerosis Shows a Network of Immune and Profibrotic Pathways Connected with Genetic Polymorphisms

Abstract: Systemic sclerosis (SSc) is a rare systemic autoimmune disease characterized by skin and organ fibrosis. The pathogenesis of SSc and its progression are poorly understood. The SSc intrinsic gene expression subsets (inflammatory, fibroproliferative, normal-like, and limited) are observed in multiple clinical cohorts of patients with SSc. Analysis of longitudinal skin biopsies suggests that a patient's subset assignment is stable over 6–12 months. Genetically, SSc is multi-factorial with many genetic risk loci f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 101 publications
7
126
2
2
Order By: Relevance
“…However, recent analyses suggest there may be stages in the progressive disease (24). Our results in longitudinal serial skin biopsy samples in the Northwestern cohort also suggest that patients may go through different intrinsic subsets as part of their progressive diseases.…”
Section: Discussionsupporting
confidence: 58%
“…However, recent analyses suggest there may be stages in the progressive disease (24). Our results in longitudinal serial skin biopsy samples in the Northwestern cohort also suggest that patients may go through different intrinsic subsets as part of their progressive diseases.…”
Section: Discussionsupporting
confidence: 58%
“…Genes with nominally significant decrease post-treatment (uncorrected p <0.05, paired t-test) in clinically significant improvers were supplied as positive examples to a SVM classifier (Greene et al, 2015) (Figure 1); genes that showed no evidence of differential expression are used as negative examples (0.95<uncorrected p≤1). The classifier learned the connectivity patterns of the DEGs in the Genome-scale Integrated Analysis of gene Networks in Tissues (GIANT) skin network and returned a ranking of all genes in the genome (Greene et al, 2015). Genes with high positive scores are most functionally similar to the nominally significant DEGs from the expression analysis (Greene et al, 2015), but are not required to be differentially expressed.…”
Section: Network-based Machine Learning Captures Known Treatment Targmentioning
confidence: 99%
“…The classifier learned the connectivity patterns of the DEGs in the Genome-scale Integrated Analysis of gene Networks in Tissues (GIANT) skin network and returned a ranking of all genes in the genome (Greene et al, 2015). Genes with high positive scores are most functionally similar to the nominally significant DEGs from the expression analysis (Greene et al, 2015), but are not required to be differentially expressed. Thus, top-ranked genes may be unregulated at the mRNA level or 'missed' due to small sample sizes, but are highly relevant to response.…”
Section: Network-based Machine Learning Captures Known Treatment Targmentioning
confidence: 99%
See 2 more Smart Citations